2021
DOI: 10.1186/s12968-021-00740-5
|View full text |Cite
|
Sign up to set email alerts
|

Defining the optimal temporal and spatial resolution for cardiovascular magnetic resonance imaging feature tracking

Abstract: Background Myocardial deformation analyses using cardiovascular magnetic resonance (CMR) feature tracking (CMR-FT) have incremental value in the assessment of cardiac function beyond volumetric analyses. Since guidelines do not recommend specific imaging parameters, we aimed to define optimal spatial and temporal resolutions for CMR cine images to enable reliable post-processing. Methods Intra- and inter-observer reproducibility was assessed in 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Higher temporal resolutions could increase the comparability of the local patterns and reduce the effect of image de‐correlation, achieving higher accuracy 15 . In our study, greater GCS and GRS and associated SRs were obtained with the higher temporal resolution acquisitions, which is consistent with data from a previous STE study 20 and other recent findings 1,22 . Since the regional magnitude of deformation is related to global function performance, as assessed by LVEF, and the frame rate is dependent on HR, 26,27 we also conducted analyses depending on LVEF and HR.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Higher temporal resolutions could increase the comparability of the local patterns and reduce the effect of image de‐correlation, achieving higher accuracy 15 . In our study, greater GCS and GRS and associated SRs were obtained with the higher temporal resolution acquisitions, which is consistent with data from a previous STE study 20 and other recent findings 1,22 . Since the regional magnitude of deformation is related to global function performance, as assessed by LVEF, and the frame rate is dependent on HR, 26,27 we also conducted analyses depending on LVEF and HR.…”
Section: Discussionsupporting
confidence: 89%
“…This temporal resolution averaging may result in lower strain values for MR‐FT in comparison to STE 2,15 . The impact of temporal and spatial resolution on MR‐FT derived myocardial deformation indices has been discussed in a recent study which showed that global longitudinal strain (GLS) and global circumferential strain (GCS) values increased at higher frames/cycle 22 . However, the results were limited to a small sample, mainly involving healthy subjects.…”
mentioning
confidence: 99%
“…A low frame rate could potentially affect the strain values. In a study by Backhaus et al, GLS was lower when the temporal resolution was 20 time frames compared to 30, 40 and 50 times frames in 5 mm and 10 mm slices [ 43 ]. But they found no difference in GLS regarding temporal resolution when using 8 mm slice thickness, such as we did in our study.…”
Section: Limitationsmentioning
confidence: 99%
“…Although our observers were well trained and experienced, LA strain values obtained by CS cine images were signi cantly underestimated in comparison with those of segmented cine. Lower temporal resolution was an important factor for underestimation of myocardial strain, but the temporal resolutions of 39ms and 46ms had no different in uence on the value of strain [31].One possible explanation for this underestimation of CS strain is that the CS cine images with pseudo-random undersampling and iterative reconstruction present reduced signal-to-noise ratio and reduced ability to demonstrate the ne structure; therefore, LA blood pool and pericardial fat might have been included in the LA strain assessment [32]. For this reason, LA strain analysis should be conducted at the same cine sequence to follow-up in the future.…”
Section: Discussionmentioning
confidence: 94%